Predictive value and mechanism of lncRNA MANCR for pediatric severe pneumonia via miR-20a-5p / MAPK1 axis - Yuting Cai; Jiaxi Xie; Jinkai Yang (Immunobiology)
Severe community-acquired pneumonia (SCAP) significantly threats the safety of children's lives. Long non-coding RNA (lncRNA) MANCR is overexpressed in lung adenocarcinoma (LUAD) tissue, promote the proliferation, invasion, and migration, decreased cell apoptosis of LUAD cells. This study aimed to detect lncRNA MANCR levels in pediatric SCAP, and explore the diagnostic and prognostic significance of MANCR in pediatric SCAP. The mechanism of MANCR was examined in a lipopolysaccharide (LPS)-induced cell model. Serum MANCR level was detected by RT-PCR in participants. The diagnostic and prognostic value of MANCR was analyzed via ROC and KM curves. LPS constructed the pneumonia cell mode. Cell viability and apoptosis were detected by CCK-8 and flow cytometry respectively. ELISA examined the concentration of inflammatory factors. Serum MANCR level was elevated in SCAP patients. High MANCR could predict SCAP from controls (AUC = 0.852, sensitivity = 0.727, specificity = 0.836). High MANCR level is a predictor for poor prognosis of pediatric SCAP (P < 0.001, HR = 5.810, 95 %CI = 2.450–13.781). LPS inhibited cell viability and promoted apoptosis and inflammation of NCI-H1563 cells. Silence of MANCR could promote cell viability, inhibit the cell apoptosis and secretion of CRP, PCT, IL-6, IL-1β, and TNF-α via miR-20a-5p / MAPK1 axis in LPS-stimulated NCI-H1563 cells (P < 0.05). High MANCR levels in pediatric SCAP patients could predict the occurrence and poor prognosis of SCAP. MANCR knockout could inhibit cell apoptosis and inflammatory factors, and enhance cell viability via miR-20a-5p / MAPK1 axis in LPS-stimulated NCI-H1563 cells.